Uplift and lateral buckling failure mechanisms of offshore pipes buried in normally consolidated clay. (March 2021) - Seth, Debtanu; Manna, Bappaditya; Kumar, Prem; Shahu, J.T.; Fazeres-Ferradosa, T.; Taveira-Pinto, F.; Rosa-Santos, P.; Carvalho, H.
Highlights: Numerical model benchmark example is provided for a buried offshore pipeline. 2-D finite element analysis is performed to understand the pipeline-soil interaction in normally consolidated clay. Uplift and lateral buckling failure mechanisms are studied for no tension and full tension conditions. Critical capacity factors and failure mechanism of pipelines are provided and analysed. Theoretical example is given for further application to field cases. Dear Editor, Abstract: Buried offshore pipelines are crucial for the swift transportation of oils and similar fluidized materials from the oil rigs to the processing center or vice versa. In this study, a 2-D finite element analysis is performed to understand the pipeline-soil interaction, the failure mechanism of soil and the variation of capacity factors with different normalised soil properties during upward and lateral buckling of a buried offshore pipeline for no tension (NT) and full tension (FT) condition. The pipeline is installed in a normally consolidated clay bed with linearly varying undrained shear strength. The effect of embedment depth ( H ), unit weight of soil (γ'), undrained shear strength ( Su ), and roughness and tensile capacity of the pipe-soil interface on the failure mechanism and capacity factors of pipes are also studied. The current numerical model is validated first against a past numerical study, which showed a good agreement between the result obtained from the current study and the results obtained from the past study (Maitra et al., 2016). Then the failure mechanism and capacity factors are obtained, and their variation for different combinations of embedment depth and unit weight of soil are demonstrated. Both the uplift and lateral capacity factors are observed to be influenced by embedment depth and unit weight of soil. It is observed that, depending on the influencing parameters, both the uplift and lateral capacity factors can be critical for the buckling of the pipeline. Several displacement diagrams are presented to show the failure mechanisms clearly, while, the stress contours are given to observe the behavior of principal effective stresses during different failure mechanisms.